UTILIZING KNOWORD TO IMPROVE VOCABULARY ACQUISITION IN HIGH SCHOOL STUDENTS - Marsevani, Maya; Sasmi, Nafa Indah; Zaki, Leil Badrah (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study aims to investigate the effectiveness of Knoword, a gamified online tool, in improving students' vocabulary acquisition. Vocabulary mastery plays a crucial role in language learning, yet many students, particularly in public schools, struggle with insufficient vocabulary knowledge due to factors like low engagement and traditional teaching methods. This research addresses these challenges by exploring how digital tools can enhance learning outcomes. The study employed Classroom Action Research (CAR) as the methodology, conducted in a public high school in Batam with 42 students in the 10th grade. The research process consisted of a learning cycle involving planning, action, observation, and reflection. Pre-tests and post-tests were administered to measure students’ vocabulary skills before and after implementing Knoword. Observations during classroom sessions also provided qualitative data on student engagement and motivation. The results showed a significant improvement in students' vocabulary acquisition. The average pre-test score was 51.59, categorized as poor, while the post-test score increased to 83.05, classified as good, with a 31.47% improvement. The findings indicate that the use of Knoword enhanced students' motivation, engagement, and vocabulary retention, making it an effective tool for vocabulary learning. The study concludes that incorporating gamified learning platforms can significantly improve vocabulary acquisition and student outcomes, especially in educational environments where traditional methods have shown limited effectiveness.